Whole exome sequencing identified a novel single base pair insertion mutation in the EYS gene in a six generation family with retinitis pigmentosa. (28th May 2017) - Hashmi, Jamil Amjad; Albarry, Maan Abdullah; Almatrafi, Ahmed M.; Albalawi, Alia M.; Mahmood, Amer; Basit, Sulman
Abstract: Retinitis pigmentosa (RP) is a group of inherited progressive retinal dystrophies (RD) and is characterized by photoreceptor degeneration. RP is clinically and genetically heterogeneous disorder. More than 70 genes are known and, thus, identification of causative genes and mutations in known genes is challenging. This study was designed to identify the underlying genetic defect in a large extended Saudi family with multiple RP affected members. Fundus photography, Optical Coherence Tomography (OCT) and visual field perimetry were performed for affected individuals. Whole exome sequencing was used to detect the underlying genetic defect in a large family with 12 affected individuals showing autosomal recessive isolated RP. WES data analysis identified a novel insertion mutation in the EYS (eyes shut homolog) gene (c.910_911insT; p.Trp304LeufsTer8). Sanger sequencing validates the variant discovered through exome in all 12 affected individuals and showed that this mutation is segregating with RP phenotype in an autosomal recessive manner in 51 individuals of the family tested here. Our study expands the mutation spectrum of EYS gene in RP patients and extends the body of evidence that supports the importance of EYS gene in eye development.